Short but not Sweet : New Evidence on Short Duration Morbidities from India - Das, Jishnu (World Bank, Washington, DC, 2014)
India spends 6 percent of its GDP on health-three times the amount spent by Indonesia and twice that of China-and spending on non-chronic morbidities is three times that of chronic illnesses. It is normally assumed that the high spending on non-chronic illnesses reflects the prevalence of morbidities with high case-fatality or case-disability ratios. But there is little data that can be used to separate out spending by type of illness. The authors address this issue with a unique dataset where 1,621 individuals in Delhi were observed for 16 weeks through detailed weekly interviews on morbidity and health-seeking behavior. The authors' findings are surprising and contrary to the normal view of health spending. They define a new class of illnesses as "short duration morbidities" if they are classified as non-chronic in the international classification of disease and are medically expected to last less than two weeks. The authors show that short duration morbidities are important in terms of prevalence, practitioner visits, and household health expenditure: Individuals report a short duration morbidity in one out of every five weeks. Moreover, one out of every three weeks reported with a short duration morbidity results in a doctor visit, and each week sick with such a morbidity increases health expenditure by 25 percent. Further, the absolute spending on short duration morbidities is similar across poor and rich income households. The authors discuss the implications of these findings in understanding household health behavior in an urban context, with special emphasis on the role of information in health-seeking behavior.